OpenStack cloud computing cookbook : over 110 effective recipes to help you build and operate OpenStack cloud computing, storage, networking, and automation.: over 110 effective recipes to help you build and operate OpenStack cloud computing, storage, networking, and automation. (2015) - Jackson, Kevin; Bunch, Cody; Sigler, Egle
No abstract available